Computational analysis of A-Pillar vortex formation in automotive applications - Bhambra, Devinder Pal Singh (Cranfield University, 2013)
The research focusses on computational analysis of vortex generation behind A-Pillar of simplified model derived from Jaguar XF that excludes air from the underside of vehicle. This vortex formation contributes in generating wall pressure fluctuations especially at speeds higher than 100km/hr. It is a collaborative work between Cranfield University and Jaguar Land Rover. Three dimensional pressure based incompressible flow using Large Eddy Simulation turbulence model is selected for computational analysis in FLUENT v14. This used high parallel computing systems available in Cranfield University. In the initial phase, three grid resolutions (coarse, medium and fine) were prepared in ICEM CFD with fine case consisting of 10 million cells. Qualitative analysis includes extraction of slices, 3-D and surface streamlines and pressure and velocity contours for capturing the unsteadiness due to the vortex formation over the front side glass surface. The iso-surface of Q captures the unsteadiness at the A-Pillar wake and side mirror wake over front side glass surface. It also reveals that the range of length scales captured were limited even at the finest grid resolution. Quantitative analysis compares the mean pressure (Cp) data with JLR results. Probes were located at 51 locations over the front side glass window that showed a good comparison; specifically for the fine grid; with maximum variation incurred at probes located in separation areas. For predicting the wall pressure fluctuations, a total of ten probes were located over the front side glass window surface. The surface pressure (static) data was recorded for 1 sec of flow-time and later imported in MATLAB for post-processing. The results obtained in 1/3rd octave band showed that the large scales were too energetic and small scales are not captured. However, comparing sound pressure levels with the Aero-acoustic Wind Tunnel (AWT); provided by JLR; it is concluded that either the grid is too coarse to resolve higher frequencies or the numerical modelling used is too dissipative to benefits the use of LES.
Keywords: Large Eddy Simulations; Sound Pressure Levels; iso-surface of Q; wall pressure fluctuations